First report of Lonchaeidae (Diptera) infesting fruits of Byrsonima crassifolia in Brazil - ADAIME, RICARDO; STRIKIS, PEDRO CARLOS; DE SOUZA-FILHO, MIGUEL F.; LIMA, CAMILA R.; LASA, RODRIGO (Revista Colombiana de Entomología, 2012)
Neosilba zadolicha and Neosilba bella (Diptera: Lonchaeidae) are reported for the first time in fruits of Byrsonima crassifolia (Malpighiaceae) in Brazil. They are considered occasional species on this tropical fruit.